Proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017). Vol. 2, - Šilhavý, Radek; Šenkeřík, Roman; Oplatková, Zuzana; Prokopová, Zdeňka; Šilhavý, Petr (Advances in intelligent systems and computing ;, 2017)
This book presents new methods for and approaches to real-world problems as well as exploratory research describing novel mathematics and cybernetics applications in intelligent systems. It focuses on modern trends in selected fields of technological systems and automation control theory. It also introduces new algorithms, methods and applications of intelligent systems in automation, technological and industrial applications. This book constitutes the refereed proceedings of the Cybernetics and Mathematics Applications in Intelligent Systems Section of the 6th Computer Science On-line Conference 2017 (CSOC 2017), held in April 2017.